Preparation and Characterization of Natamycin Loaded Bioadhesive In Situ Ophthalmic Gel for Enhanced Bioavailability - Verma, Pankaj; Gupta, Vandana; Manigauha, Ashish (Journal of Sustainable Materials Processing and Management, 2022)
Natamycin is used in the antifungal preparation of eye drops. The eye drop needs frequent installation into the eye and also having poor bioavailability. The present study was planned to formulate and characterized in situ ophthalmic gel of Natamycin by using a blend polymer of sodium alginate, ethylcellulose, and Xanthan gum for better residence time and bioavailability of the drug. The six different formulations (F1 to F6) of Natamycin in situ gel were prepared. All the formulations were evaluated for clarity, visual appearance, pH, gelling capacity, drug content, assessment of drug release, kinetic modeling, ocular irritancy, and stability study. The results were found to have complied with the Pharmacopoeial specification. The in vitro drug releases of F3 established maximum drug release for 8 hrs compared to other formulations and showed sustained release. Further, the F3 was stable and showed non-irritant and safe to use. The studies suggested that prepared in situ ophthalmic gel of Natamycin will be an alternative for conventional eye drops and a valuable alternative to counter the precorneal loss.